2021
DOI: 10.3389/fpsyg.2021.625584
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between K-Workers’ Leader–Member Exchange, Organizational Citizenship Behavior and Task Performance—Evidence From Chinese Hospitals

Abstract: Aiming to reduce the difficulty of managing and motivating knowledge workers (k-workers), and promote the psychological well-being of them in Chinese hospitals, this study examines how k-workers’ leader–member exchange (LMX) influences their task performance and the mediation effect of organizational citizenship behavior (OCB). Through a self-administered survey, valid questionnaires were collected from 384 k-workers in Chinese hospitals, and partial least squares structural equation modeling was employed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Research on LMX suggests that high-quality LMX increasingly engenders feelings of mutual obligation and reciprocity, which triggers employees’ positive work behavior ( Dulebohn et al, 2012 ). Previous research has consistently shown that LMX is positively related to task performance and OCB ( Breevaart et al, 2015 ; Anand et al, 2018 ; Che et al, 2021 ; Park et al, 2022 ). Task performance refers to “the basic required duties of a particular job.” ( Ng and Feldman, 2010 , p. 1223).…”
Section: Theory and Hypothesesmentioning
confidence: 88%
“…Research on LMX suggests that high-quality LMX increasingly engenders feelings of mutual obligation and reciprocity, which triggers employees’ positive work behavior ( Dulebohn et al, 2012 ). Previous research has consistently shown that LMX is positively related to task performance and OCB ( Breevaart et al, 2015 ; Anand et al, 2018 ; Che et al, 2021 ; Park et al, 2022 ). Task performance refers to “the basic required duties of a particular job.” ( Ng and Feldman, 2010 , p. 1223).…”
Section: Theory and Hypothesesmentioning
confidence: 88%
“…Che et al (2021) observed that LMX significantly relates to the OCB of the nurses in the pandemic situation.…”
Section: Review Of Literaturementioning
confidence: 96%
“…Support of the supervisor in the form of positive LMX is a job resource under the job demands resources model of Bakker and Demerouti (2007); nurses burdened with a heavy workload in pandemic look for support from the immediate boss and remain ready to work extra to maintain the relationship. Che et al (2021) observed that LMX significantly relates to the OCB of the nurses in the pandemic situation.…”
Section: Ocb Of Nurses In Covid-19 Pandemicmentioning
confidence: 96%
“…First, according to LMX theory, leaders are an important situational variable affecting employee innovation behaviour (He et al, 2019;Koh et al, 2019). Therefore, the exchange relationship between leaders and subordinates should be a key factor in explaining employee behaviour (Che et al, 2021). In organisations with a strong organisational political atmosphere, employees with more political skills are better at establishing and maintaining good relationships with leaders and becoming their 'insiders", thereby promoting their own career development (Liu et al, 2008).…”
Section: Organisational Political Climate and Employees' Innovative B...mentioning
confidence: 99%